Producing Staged Videos for Teacher Education: Development and Content Validation of Video Scripts on the Topic of Handling Classroom Disruptions - Maxie Kilbury; Anja Böhnke; Felicitas Thiel (MDPI AG, 2023)
Video-based teacher training has become an important component of teacher education. A special form of instructional videos is scripted videos, also known as staged videos. They can be used to accomplish several didactic objectives and visualise problematic situations, such as severe classroom disruptions caused by specific behavioural motives, which are very difficult to videotape in a real classroom. However, reservations exist due to limited authenticity, and thus content validity of staged videos. This paper describes the process of a theory-led script development as the key role for authentic and valid scripts. Therefore, we refine four crucial criteria, relevant, engaging, challenging, and realistic, for staged videos dealing with classroom disruptions. We show the content-validation process with reference to the applied theory-led criteria. A key output of this study is a manual for the development of scripted videos which will be perceived as authentic, and which reach the intended cognitive demands. An expert validation and two evaluative studies with data from 274 and 70 preservice teachers confirm the success of the final products.